2012
DOI: 10.1590/s0004-282x2012000100016
|View full text |Cite
|
Sign up to set email alerts
|

Facial somatosensorial evaluation in idiopathic trigeminal neuralgia

Abstract: Idiopathic trigeminal neuralgia (ITN) is identified by paroxysmal unilateral shock-like pain, distributed in one or more trigeminal branches, with clear diagnostic criteria based on history and clinical exams. Etiology and physiopathology remain obscure. Recently, abnormal expression of voltage-gated sodium channels had been described in these patients, suggesting that ITN could be a channelopathy 1 . Current diagnostic criteria do not include sensorial deficit; however, recent studies have shown that discrete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
(5 reference statements)
1
2
0
Order By: Relevance
“…In addition, subjective visual and auditory abnormalities were identified in patients with trigeminal neuralgia treated with trigeminal ganglion microcompression 22 . These studies were confirmed by further studies [23][24][25] . It is also important to stress the involvement of voltage-gated sodium channels in trigeminal neuralgia.…”
Section: Trigeminal Neuralgiasupporting
confidence: 64%
“…In addition, subjective visual and auditory abnormalities were identified in patients with trigeminal neuralgia treated with trigeminal ganglion microcompression 22 . These studies were confirmed by further studies [23][24][25] . It is also important to stress the involvement of voltage-gated sodium channels in trigeminal neuralgia.…”
Section: Trigeminal Neuralgiasupporting
confidence: 64%
“…Trigeminal afferents are originated from all orofacial tissues, the dura, nasal tissues, corneal surface, and facial skin [34]. The diagnostic criteria form of ITN does not include neurological abnormalities, but light changes in sensory function have been reported [3,10,30,31,[35][36][37]. In this study, thermal detection thresholds (warm and cold) and tactile detection were higher in the group of patients (Fig.…”
Section: Gustatory Olfactory and Somatosensory Evaluationmentioning
confidence: 66%
“…But multiple drugs like gabapentin, oxcarbazepine, amitrptyline, chlorpromazine, and carbamazepine were given. Silva et al [13] reported a patient whose symptoms completely relieved only one week after initiation of carbamazepine. In our patient, we did not find any etiologic cause and evaluated idiopathic TGN.…”
Section: Discussionmentioning
confidence: 99%